Comparison of interpupillary distance and combined mesiodistal width of maxillary central incisor teeth in two ethnic groups of Northeast India: An in vivo study - Jogeswar Barman; Sangma Serin (Wolters Kluwer Medknow Publications, 2018)
Background: Anthropometric measurements of the face can be used as a guide in selecting proper sized anterior teeth. Aim: The aim of this study is to evaluate the relationship between the interpupillary distance (IPD) and the combined mesiodistal width of maxillary central incisors (MDW of MCIs) to establish their morphometric criterion and their significance in two ethnic groups of Northeast India. Methodology: A total of 120 participants consisting of 60 indigenous students each from Assam and Meghalaya in the age group of 18-25 years were selected after taking their written consent. Standardized facial frontal photographs of all the participants were taken using a digital camera in such a manner that maxillary anterior teeth were visible. The photographs were uploaded onto the computer and saved in a file. Anthropometric measurements of IPD and combined MDW of MCIs in centimeters were made using both Adobe Photoshop® 7.0 software program and manually using a digital vernier caliper on the developed photographs to a same size of 15 cm × 10 cm. Data obtained were tabulated and analyzed using Student "t"-test and Pearson correlation test. Results: The present study reveals a positive correlation with a high degree of statistical significance between IPD and combined mesiodistal width of maxillary central incisors among all the samples irrespective of gender and ethnicity where P < 0.01. Conclusion: IPD can be used as a guide in determining the suitable mesiodistal dimension of the maxillary central incisors.